Does disallowing body checking in non-elite 13- to 14-year-old ice hockey leagues reduce rates of injury and concussion? A cohort study in two Canadian provinces - Emery, C.; Palacios-Derflingher, L.; Black, A. M.; Eliason, P.; Krolikowski, M.; Spencer, N.; Kozak, S.; Schneider, K. J.; Babul, S.; Mrazik, M.; Lebrun, C. M.; Goulet, C.; et al. (British Journal of Sports Medicine, 2020)
OBJECTIVE: To compare rates of injury and concussion among non-elite (lowest 60% by division of play) Bantam (ages 13-14 years) ice hockey leagues that disallow body checking to non-elite Bantam leagues that allow body checking. METHODS: In this 2-year cohort study, Bantam non-elite ice hockey players were recruited from leagues where policy allowed body checking in games (Calgary/Edmonton 2014-2015, Edmonton 2015-2016) and where policy disallowed body checking (Kelowna/Vancouver 2014-2015, Calgary 2015-2016). All ice hockey game-related injuries resulting in medical attention, inability to complete a session and/or time loss from hockey were identified using valid injury surveillance methodology. Any player suspected of having concussion was referred to a study physician for diagnosis and management. RESULTS: 49 body checking (608 players) and 33 non-body checking teams (396 players) participated. There were 129 injuries (incidence rate (IR)=7.98/1000 hours) and 54 concussions (IR=3.34/1000 hours) in the body checking teams in games. After policy change, there were 31 injuries (IR=3.66/1000 hours) and 17 concussions (IR=2.01/1000 hours) in games. Policy disallowing body checking was associated with a lower rate of all injury (adjusted incidence rate ratio (IRR)=0.44; 95% CI: 0.27 to 0.74). The point estimate showed a lower rate of concussion (adjusted IRR=0.6; 95% CI: 0.31 to 1.18), but this was not statistically significant. CONCLUSION: Policy change disallowing body checking in non-elite Bantam ice hockey resulted in a 56% lower rate of injury. There is growing evidence that disallowing body checking in youth ice hockey is associated with fewer injuries.